2013
DOI: 10.1097/01.aog.0000433981.36184.4e
|View full text |Cite
|
Sign up to set email alerts
|

Practice Bulletin No. 138

Abstract: Inherited thrombophilias are associated with an increased risk of venous thromboembolism and also have been linked to adverse outcomes in pregnancy. However, there is limited evidence to guide screening for and management of these conditions in pregnancy. The purpose of this document is to review common thrombophilias and their association with maternal venous thromboembolism risk and adverse pregnancy outcomes, indications for screening to detect these conditions, and management options in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(36 citation statements)
references
References 30 publications
0
33
0
3
Order By: Relevance
“…However, they were not able to show any statistically significant difference for PS. From their data Paidas et al [5,6] proposed cut-off values for FPS. Authors identified 30 and 25 % cut-off values for FPS in the second and third trimesters, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they were not able to show any statistically significant difference for PS. From their data Paidas et al [5,6] proposed cut-off values for FPS. Authors identified 30 and 25 % cut-off values for FPS in the second and third trimesters, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, this decrease in protein S (PS) and FPS levels may also be offered to cause predisposition to thrombosis and PVD. In order to differentiate between normal and abnormal during pregnancy cut-off values had been previously proposed for clinical use [5,6]. However, reference curves for the gestational age in weeks for FPS haven't been established.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the risk of a thromboembolic event during pregnancy has been shown to differ according to the nature of the thrombophilia, with estimates of risk varying from 5 to 33 % [5]. Nevertheless, the routine screening of all pregnant women to identify those with thrombophilias has not been recommended and antenatal prophylaxis for all women with known thrombophilias remains controversial [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…We also identified 70 specific situations guidelines published between 2002 and 2014. Of these, 91% were from the USA,25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59 UK60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76 and Canada 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88. The remaining were from Australia,89 Brazil,90 Mexico,91 Poland,92 Spain93 and Uruguay 94…”
Section: Resultsmentioning
confidence: 99%